Clinical relevance of mediopatellar plica of the femoropatellar knee joint (literature review) - Baburkina, Elena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2020)
The problem of diagnosis and treatment of the mediopatellar plica (MP) syndrome is urgent, since the pathology of this formation has not been studied sufficiently in adults, children and adolescents. MP syndrome causes pain in the anterior knee joint in 3.25–11 % of cases. The average frequency in adult population varies from 20 to 60 %. At arthroscopy intervention, the MP was detected in 14–100 % of patients, and 25–34 % of cases were found during autopsy of the dead bodies. At normal conditions the MP is thin, corneal and flexible. In the case of an inflammatory process in the joint, it becomes swollen, thickened and affects the movement in the patella-femoral joint, determining changes in the cartilage of the knee and medial surface of the femur. In pathological MP, usually increases vascularization, it is noted hyalinization and signs of inflammation. Chronic cases of MP syndrome are characterized by fibro-cartilage metaplasia, progression of collagenosis and calcification. The most common is the classification by J. Sakakibara based on the size of the MP. Type A and B plicae are not always accompanied by symptoms; types C and D can be sandwiched between the medial growth and the knee and become thickened causing internal damage to the knee joint. The complexity of the diagnosis is due to the fact that clinical manifestations often mimic the symptoms of damage of the meniscus and ligaments. Pathology of MP is not different from the clinic of other knee injuries, except for the clear localization of pain, which is abruptly exacerbated during bending of the knee joint in the range from 150° to 110° and accompanied by a feeling of clicking. The most informative non-invasive methods of diagnosis of MP syndrome are ultrasound and MRI. For the treatment conservative and surgical methods are used. There are a small number of papers in which the authors describe the relationship between patello-femoral joint dysplasia and the presence of MP. In our opinion, the study of this issue is noteworthy. This will help to understand the causes of the syndrome, diagnosis and treatment tactics.